ANALYSING A RIGHT-WING TEXT THROUGH HALLIDAYS TRANSTIVITY SYSTEM AND CRITICAL DISCOURSE ANALYSIS - Ghobain, Dr. ELHAM (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
In this paper, I attempt to present an example of following Hallidays grammatical system in analysing a text that can bear racial references. Doing so, the text analysis can be viewed from a critical discourse analysis perspective. The text chosen, titled Europe Must Close Its Borders or be Swamped by Third World, published in 2009, exhibits a typical example of the political rhetoric used by far-right political parties represented by one of its leaders in Britain, Nick Griffin. My assumption is that every word, every verb, and every phrase used is carefully chosen to convey the intended agendas of the party to its prospect voters in a clever way, which achieves its maximum effect with little or no apparent violation to the press guidelines. I also believe that such a stirring text, as far as the paper is concerned, would benefit from the use of various types of verbs and phrases that should suffice the requirement of the analysis. The paper may be of good use to students interested in studying this system of analysis as it deeply goes into the details of the used text.